KAJIAN EKSPRESI PROTEIN BAX PADA GANGGUAN SPERMATOGENESIS PASCA PEMAPARAN 2,5-HEXANADIONE, PADA TIKUS PUTIH (RATTUS NORVEGICUS L) - -, MAHRIANI (2008)
Keywords: Expression; protein Bax; Spermatogenesis; 2,5-Hexanadione; Rattus norvegicus L

(untitled) (Jurnal Biologi Udayana, 2008)
The disturbance of spermatogenesis after exposure with 2,5-HD (2,5-Hexanedione) can be observed through the increasing of death cell in apoptosis mechanism, that can be observed through the expression of Bax protein. Therefore, it had been conducted a research to study the expression of Bax protein against white mouse of Wistar strain exposured with 2,5-HD. A number of 56 white mouse were divided randomly into 8 groups, each group consists of 7 white mouse, two groups were used as pretest, three groups used as control treatment, and three groups used as treatment were exposured with 2,5-HD of 0,06 mg/WW during 2, 4, 6 week. The changes in the Bax protein expression observed in the slices of cross section of testis using imunohistochemical method. The research result shows that the longer duration of 2,5-HD exposure causes the more increase the expression of Bax protein at the sertoli cell and the germinal. The expression of Bax protein compared to the control groups increases into 132%, 112%, 108% and 123% respectively for the sertoli, spermatogonial, spermatocyt, and spermatid cells in the treatment were exposured with 2,5-HD during 6 weeks. It is needed a further research to complete information of apoptosis mechanism as the result of 2,5-HD exposure, by study the ratio of Bcl-2/Bax expression as the antiapoptosis and proapoptosis proteins.